Insulinemic Potential of Lifestyle Is Inversely Associated with Leukocyte Mitochondrial DNA Copy Number in US White Adults. Issue 8 (3rd June 2020) - Yang, Keming; Forman, Michele R; Monahan, Patrick O; Graham, Brett H; Chan, Andrew T; Zhang, Xuehong; De Vivo, Immaculata; Giovannucci, Edward L; Tabung, Fred K; Nan, Hongmei
ABSTRACT: Background: Poor lifestyles have been linked to insulin insensitivity/hyperinsulinemia, which may contribute to downstream changes such as inflammation and oxidative damage and the development of chronic diseases. As a biomarker of intracellular oxidative stress, leukocyte mitochondrial DNA copy number (mtDNA-CN) has been related to lifestyle factors including diet and weight. No epidemiologic study has examined the relation between combined insulinemic potential of lifestyle and mtDNA-CN. Objectives: Our aim was to examine the association between Empirical Lifestyle Index for Hyperinsulinemia (ELIH) and leukocyte mtDNA-CN in US men and women. Methods: This cross-sectional analysis included 2835 white adults without cancers, diabetes, or cardiovascular disease at blood collection, including 2160 women from the Nurses' Health Study and 675 men from the Health Professionals Follow-Up Study. ELIH is an index based on plasma C-peptide that characterizes the insulinemic potential of lifestyle (diet, body weight, and physical activity). Relative mtDNA-CN in peripheral blood leukocytes was measured by qPCR-based assay. Results: We found a significant inverse association between ELIH and mtDNA-CN. In multivariable-adjusted linear models, absolute least squares means ± SDs of mtDNA-CN z score across ELIH quintiles in women were as follows: Q1: 0.14 ± 0.05; Q2: 0.04 ± 0.06; Q3: 0.008 ± 0.05; Q4: 0.01 ± 0.05; and Q5: −0.06 ± 0.05 ( P -trend = 0.006). Means ± SDs in men were as follows: Q1: 0.25 ± 0.09; Q2: 0.23 ± 0.09; Q3: 0.07 ± 0.09; Q4: 0.02 ± 0.09; and Q5: −0.04 ± 0.09 ( P -trend = 0.007). Means ± SDs in all participants were as follows: Q1: 0.16 ± 0.05; Q2: 0.07 ± 0.05; Q3: 0.01 ± 0.05; Q4: 0.01 ± 0.05; and Q5: −0.05 ± 0.05 ( P -trend = 0.0004). Conclusions: Hyperinsulinemic lifestyles (i.e., higher ELIH) were associated with lower leukocyte mtDNA-CN among subjects without major diseases, suggesting that the difference in lifestyle insulinemic potential may be related to excessive oxidative stress damage.